Pelatihan Pengolahan Dan Visualisasi Data Sebagai Penunjang Peningkatan Pendidikan Menggunakan Microsoft Excel - Hasanuddin Al-Habib; Yuliani Puji Astuti; Fadhilah Qalbi Annisa; Riskyana Dewi Intan Puspitasari; Harmon Prayogi; Ulfa Siti Nuraini (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2025)
The aim of the community service to provide training and mentoring in educational data processing using Microsoft Excel. The community service activity involves teachers as participant from Sekolah Indonesia Bangkok, Thailand. The activities are carried out in phases which include planning, coordination with partner school, obtaining necessary permits, developing training module, conducting the training, and evaluating the outcomes. The training consisted of four stages which are a pre-test, training material presentation, a question-and-answer session, and a post-test. The output of the community service was a Microsoft Excel training module that cover both the technical aspects of the software and simple practical application. The effectiveness of the training was evaluated based on the results of the pre-test and post-test. The result showed a significant improvement regarding to participants’ understanding, as evidenced by the increase in the number of correct answers and the average percentage between the pre-test and post-test. The average percentage of correct answers of the participants before the training was around 34% and after the training about 52%. Meanwhile, the average percentage of the pre-test is 62,27% and post-test is 87,91%.